RANCANG BANGUN KRAN AIR TANPA SENTUH BERBASIS SENSOR INFRA MERAH - Pebri Prihatmoko (Pusat Riset dan Inovasi Nasional, 2022)
Covid 19 is a disease caused by the corona virus that originated in China. This virus can spread through solid, liquid and airborne droplets. There is no cure for this disease, so only preventive measures can be taken. Preventive measures include wearing masks and washing hands frequently with soap. One of the equipment that is often used to wash hands is a water faucet. In general, to open the valve, the faucet handle must be turned by hand. In the process of opening this valve, it has the potential to be a medium for the spread of the corona virus, considering that in general, faucets are used interchangeably using a hand touch. The purpose of this research is to change the manual water faucet into a water faucet that is operated without a touch of the hand. The method used in this study is a switch based on an infrared sensor. The result of this study is a water faucet unit that operates without the touch of a hand.